Verbal fluency and semantic association deficits in children with in birth nonprogressive neuromuscular diseases - Koriakina, Maria; Agranovich, Olga E.; Ntoumanis, Ioannis; Ulanov, Maxim; Blank, Isak B.; Shestakova, Anna; Blagovechtchenski, Evgeny (Frontiers in Human Neuroscience, 2025)
IntroductionThe relationship between motor and cognitive skills is a pivotal issue in neuroscience, with embodied cognition theory asserting that bodily actions and experiences play a vital role in cognitive processing. This relevance is particularly noted in children with severe motor disorders (MD) from birth, highlighting a need to explore how these disorders may impede cognitive functions.MethodsIn this study, we assessed verbal fluency, a critical component of speech function, in 68 children aged 7 to 15. This group consisted of 36 children with motor disorders, specifically those diagnosed with obstetric brachial plexus palsy (OBPP, n = 22) or arthrogryposis multiplex congenita (AMC, n = 14), and 32 healthy control children. We compared levels of verbal fluency, action/verbal naming, and the development of semantic associations between the two groups.ResultsThe findings revealed that children with motor impairments exhibited significantly lower performance in tasks measuring verbal fluency and semantic association compared to the control group. Mainly, MD children produced fewer words during verbal fluency tasks and demonstrated reduced semantic associations. Interestingly, MD children with unilateral limb impairment outperformed those with bilateral impairment on semantic association tasks.DiscussionThese results suggest that the cognitive deficits observed in children with motor impairments can be attributed to less engagement with their physical environment, which influences their ability to perceive and manipulate objects differently based on their level of impairment. Additionally, the findings underscore how social and cultural contexts may be affected by motor impairments. Overall, our study supports the concept of embodied cognition, demonstrating that delays in motor skill development among children with OBPP and AMC can harm their cognitive functions.